Asuhan Keperawatan Terapi Menggambar Terhadap Fungsi Kognitif pada Lansia dengan Demensia di PSBDBB 2 Cengkareng - Amanda_nurrohman10. revangga; Mia Atlantic (Jurnal Kesehatan STIKes Sumber Waras, 2025)
Background: the elderly experience various health problems, one of which is impaired cognitive function, one type of cognitive function disorder that is common in the elderly is, characterized by complaints from respondents such as not remembering dates, days, years, feeling dissatisfied with their lives. Therefore, the main nursing diagnosis is memory impairment related to the aging process. One of them handles cognitive function disorders non-pharmacologically, namely by providing drawing therapy. Objective: to provide nursing care to reduce cognitive function by providing drawing therapy for the elderly. Method: case study of 2 respondents by providing intervention for 5 days. Researcher results: in respondent I and respondent Translated with DeepL.com (free version) II obtained, namely after being given the intervention of giving drawing therapy, respondent I from the MMSE score of moderate cognitive function decline (20) to no cognitive function impairment with MMSE score (28) while respondent II from the MMSE score of severe cognitive function decline (10) to no cognitive function impairment with MMSE score (24). Conclusion: drawing therapy is proven effective to reduce cognitive function in the elderly.